Mathematics as a Career Desire: A Survey of Students among Mechi Multiple Campus - Shah, Binod (Adhyayan Journal, 2022)
The purpose of this study was to find out how Mechi Multiple Campus students feel about mathematics as a career option. The study was conducted using a descriptive research approach. A structured questionnaire was used to obtain primary data from a random sample of 435 pupils. To arrive at a conclusion, the data was processed using the mean and standard deviation. The findings suggest that pupils were not interested in pursuing mathematics as a career. Students would rather pursue professions in disciplines other than math. They were also hesitant to spend adequate time, effort, and determination to improve their mathematic skills.